Factors that dominate the selection of off-campus private rental housing / Mohd Ikhwan Ilmi bin Mohd Alwi and Abdul Muhaimin Ab. Wahid - Mohd Alwi, Mohd Ikhwan Ilmi; Ab. Wahid, Abdul Muhaimin (2019)
The current inclination of housing development and rapid enrolment change are impacting students' daily life such as their convenience, housing comfort and safety. Thus, would demand on the increase in learning spaces, residential facilities and supporting facilities. However, the emphasis had been on providing student housing for living on-campus while living off-campus had been neglected. Therefore, students like any other human being, housing is their basic needs and having convenience housing will lead to contented life. Lately, issues on parallel session of Diploma and Degree session happened and contributed on inadequacy of hostel accommodation in the campus. Then, the students have to rent offcampus residential facilities on their own. This research is undertaken to find out students perception towards rental housing accommodation. This study requires a questionnaire survey from the active and prominent NR students. The data has been analyzed by using SPSS version 24. Thus, the result indicated that majority of respondent agreed that location nearby to the campus is their most preferable to stay. Then, that result would relate to the aim of this research. The significant of this contribution will help the owner of rental housing market to improve services on their dwellings for tenant satisfaction.